2015
DOI: 10.1167/15.9.8
|View full text |Cite
|
Sign up to set email alerts
|

Eyes on emergence: Fast detection yet slow recognition of emerging images

Abstract: Visual object recognition occurs at the intersection of visual perception and visual cognition. It typically occurs very fast and it has therefore been difficult to disentangle its constituent processes. Recognition time can be extended when using images with emergent properties, suggesting they may help examining how visual recognition unfolds over time. Until now, their use has been constrained by limited availability. We used a set of stimuli with emergent properties-akin to the famous Gestalt image of a Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition, the use of visual stimuli and blurred transitions reduces the demand for working memory, cross-modal integration and configurement of mental representations. Alternative cueing methods, such as non-sequential paradigms and semantic cues, are sufficient to trigger perceptual reorganisation in adults (González-García et al, 2018; Ludmer et al, 2011; Nordhjem et al, 2015; Samaha et al, 2018). While in the present study we prioritised reducing load for cross-modal and working-memory processes known to concurrently develop throughout childhood (Buss et al, 2018; Jüttner et al, 2006; Swanson, 2017), future work should test how these processes affect cue integration across development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of visual stimuli and blurred transitions reduces the demand for working memory, cross-modal integration and configurement of mental representations. Alternative cueing methods, such as non-sequential paradigms and semantic cues, are sufficient to trigger perceptual reorganisation in adults (González-García et al, 2018; Ludmer et al, 2011; Nordhjem et al, 2015; Samaha et al, 2018). While in the present study we prioritised reducing load for cross-modal and working-memory processes known to concurrently develop throughout childhood (Buss et al, 2018; Jüttner et al, 2006; Swanson, 2017), future work should test how these processes affect cue integration across development.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the actual format of the prior induced with this kind of Mooney templates. A recent study in TD participants showed that word primes (e.g., “gorilla” if the Mooney contained a gorilla) or image primes of different exemplars of the same category as the object in the Mooney image (Nordhjem, Kurman Petrozzelli, Gravel, Renken, & Cornelissen, 2015) helped recognition as well, suggesting that an activation of a conceptual prior is sometimes sufficient to improve Mooney perception. Indeed, neural changes related to prior information for Mooney images can be found both in higher-level visual and in lower-level retinotopic areas, and those activity patterns are different from the neural correlates of conventional (feature-based) priming (Gorlin et al, 2012; Hsieh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative cueing methods, such as non-sequential paradigms and semantic cues, are sufficient to trigger perceptual reorganization in adults. 25 , 40 , 41 , 42 While in the present study we prioritized reducing load for cross-modal and working-memory processes known to concurrently develop throughout childhood, 43 , 44 , 45 future work should test how these processes affect cue integration across development.…”
Section: Discussionmentioning
confidence: 99%